Impact of Violence on Female Students’ Mental Health and Academic Performance in Social Studies in College of Education Gidan-Waya Kaduna State Nigeria - Endurance Nuhu (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
The study investigated the impact of violence on the mental health and academic performance of female Social Studies students in NCE II in College of Education, Gidan-Waya, Kaduna State, Nigeria. Four research questions and four hypotheses were answered and tested in the study. The study adopted a descriptive survey research design. The population consisted of all 840 female NCE II students and a sample of 370 students were selected using simple random sampling technique. Two structured instruments titled: The Impact of Violence on Female Students’ Mental Health in Social Studies Questionnaire and Impact of Violence on Female Students’ Academic Performance in Social Studies were developed on a five-point Likert scale. The validity was established through expert review and pilot testing, while reliability was confirmed with a Cronbach’s Alpha coefficient of 0.84. Data were collected with the assistance of trained female research assistants and analyzed using descriptive statistics (frequency, mean, standard deviation) and inferential statistics (Chi-square tests) at a 0.05 level of significance. Findings revealed that violence is significantly prevalent among female students and has a substantial negative effect on their mental health, leading to anxiety, depression, and emotional withdrawal. Academic performance was also found to be negatively affected, manifesting in absenteeism, poor concentration, and low achievement. Coping strategies ranged from adaptive mechanisms such as counseling and creative engagement to maladaptive responses such as self-isolation. The study concludes that violence against female students represents a profound educational and psychological crisis that hampers their learning and well-being. It recommends the establishment of gender-sensitive support units with professional counselors, mandatory anti-violence training for staff, integration of awareness programs into NCE curricula, improved campus security measures, and the creation of peer-support networks to empower female students. These measures are essential for fostering safer, more inclusive, and academically supportive environments in Nigerian Colleges of Education.